Análisis, diseño y maquetación de un sitio web para la empresa “Calzado Ale” partiendo de la utilización de una metodología para cumplir parámetros de usabilidad - Condo Guaraca, Diego Ivan (2024)
Currently, the Internet is part of the evolutionary process of the user and companies, which is why they see the need to promote services and provide adequate communication, providing immediate accessibility to negotiation on the extensive network through a tool that has become a vital part of everyday life, as is a website that, with accurate information, a user-friendly and pleasant interface and quick access, covers the needs that the site visitor requires, which is why the development of websites that help to provide a quality service that is fast, concise and accurate in information and functionality. The website is currently the essential means to publicize, sell, or advertise quickly with global reach; this extends to companies that market products and services, to self-employed professionals, to people or organizations that act on a non-profit basis, trying to disseminate their works, concerns, or ideas; just like social networks that used media today.